2010
DOI: 10.1021/jp912205y
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Imidazolium Based Ionic Liquid on the Pore Surface of Nanoporous Materials—Study of Physicochemical and Thermodynamic Properties

Abstract: Supported ionic liquid phase (SILP) systems were prepared by immobilizing a methylimidazolium cation based ionic liquid onto the pore surface of two types of support, MCM-41 and Vycor. The "grafting to" method was applied, involving (3-chloropropyl)-trialkoxysilane anchoring on the supports' silanol groups, followed by treatment with 1-methylimidazole and ion exchange with PF(6)(-). Optimum surface pretreatment procedures and reaction conditions for enhanced ionic liquid (IL) loading were properly defined and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…There are a number of advantages of ILs in separation and reaction systems, but in many cases there is a need to immobilize them on porous materials (Wasserscheid and Welton 2008). The supported ILs can be spread on the inner surface of the porous structure, maintaining large specific surface area and mechanical properties of the support, thus circumventing the problem of mass transport limitation and the need for high amounts of ILs (Zhang et al 2009a;Vangeli et al 2010). The resulting material is usually referred as supported ionic liquid phase (SILP).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are a number of advantages of ILs in separation and reaction systems, but in many cases there is a need to immobilize them on porous materials (Wasserscheid and Welton 2008). The supported ILs can be spread on the inner surface of the porous structure, maintaining large specific surface area and mechanical properties of the support, thus circumventing the problem of mass transport limitation and the need for high amounts of ILs (Zhang et al 2009a;Vangeli et al 2010). The resulting material is usually referred as supported ionic liquid phase (SILP).…”
Section: Introductionmentioning
confidence: 99%
“…They can be grouped into three classes based on their pore diameter: microporous, d < 2.0 nm; mesoporous, 2.0 < d < 50 nm; and macroporous, d > 50 nm (Zhang et al 2009b). A diversity of support materials were selected of different chemical nature among those commonly used in SILP preparation, like TiO 2 (Chen et al 2007), SiO 2 (Zhang et al 2009a;Vangeli et al 2010;Fang et al 2010;Mehnert 2005) or AC (Virtanen et al 2009a;Kohler et al 2010) among others (Riisager et al 2006b). In an earlier work, Palomar et al (2009) showed the possibility of following the amount of imidazolium-based IL on AC supports by measuring the percentage of elemental nitrogen in SILP from EA and it has been herein extended to several supports and SILP systems in order to generalize the use of this technique for direct quantification of IL loaded on SILP materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inorganic-organic hybrid [1][2][3][4][5][6][7][8] materials have attracted considerable interest as the combination of the features of different parts can generate high performance. As the development of nanoscale materials, SiO 2 has indeed stimulated remarkable scientific interest because of its excellent performance and promising applications in scientific and technological fields.…”
Section: Introductionmentioning
confidence: 99%